2021
DOI: 10.1097/j.pain.0000000000002512
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in pain perception during acute SARS-CoV-2 infection: a case series

Abstract: Temporary chronic pain reduction related to acute COVID-19 has been observed, providing new knowledge on the possible mechanisms of pain modulation and potential therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…From a mechanical hypersensitivity perspective, this model aligns with the somatosensory trajectory, both acute and chronic, of many patients with COVID-19. For example, our findings align with other hypotheses and reports that acute SARS-CoV-2 infection may attenuate existing pain or reduce expected myalgic hypersensitivity due to viral infection ( 60 , 121 ) but may also result in prolonged pain symptoms ( 122 ). This SARS-CoV-2 model was also useful for further identifying core mechanisms across pain models while also potentially providing insights into the viral-mediated nociceptive states that are relevant for drug development.…”
Section: Discussionsupporting
confidence: 91%
“…From a mechanical hypersensitivity perspective, this model aligns with the somatosensory trajectory, both acute and chronic, of many patients with COVID-19. For example, our findings align with other hypotheses and reports that acute SARS-CoV-2 infection may attenuate existing pain or reduce expected myalgic hypersensitivity due to viral infection ( 60 , 121 ) but may also result in prolonged pain symptoms ( 122 ). This SARS-CoV-2 model was also useful for further identifying core mechanisms across pain models while also potentially providing insights into the viral-mediated nociceptive states that are relevant for drug development.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, breathlessness is defined as a subjective experience, with physiological and affective manifestations [ 33 ]. Distinct neuronal pathways have been demonstrated for these manifestations, with affective dimensions of breathlessness associated with the limbic system, whereby information from vagal afferents in the lungs projects to the amygdala, medial dorsal areas of the thalamus and the insula [ 63 ]. Importantly, the limbic system is also associated with PTSS [ 64 ], with evidence to suggest that interactions between breathlessness and PTSS may manifest in this emotional neural network.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is a hallmark symptom reported in individuals with acute SARS‐CoV‐2 infection, as well as in long‐COVID (Augustin et al, 2021; Carfi et al, 2020). However, a growing number of case studies have reported reductions in chronic disease‐related pain during and following infection with SARS‐CoV‐2 (Hentsch et al, 2021). Further, some evidence exists to suggest an analgesic role for the SARS‐CoV‐2 spike protein via blocking of vascular endothelial growth factor‐A signaling (Moutal et al, 2021).…”
Section: Discussionmentioning
confidence: 99%